Efficient synthesis of 5-(hydroxymethyl)furfural esters from polymeric carbohydrates using 5-(chloromethyl)furfural as a reactive intermediate - Bhat, Navya Subray; Hegde, Shobhita L.; Dutta, Saikat; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2022)
This work reports an efficient, gram-scale synthesis of 5-(hydroxymethyl)furfural (HMF) esters using biomass-derived 5-(chloromethyl)furfural (CMF) as a reactive intermediate. The HMF-esters have potential applications as chemicalintermediates, fuel additives, and bioactive compounds. Initially, CMF was prepared in good yields directly from polymericcarbohydrates (starch, inulin, and cellulose) and cellulosic materials (cotton andfilter paper) using a biphasic batch reaction system,consisting of aqueous hydrochloric acid and 1,2-dichloroethane. The use of ZnCl2as an additive allowed the reaction to proceedunder milder conditions while significantly improving the isolated yield of CMF. The effects of reaction temperature, reaction time,extracting solvent, and ZnCl2loading on CMF yield were investigated. Microcrystalline cellulose was converted into CMF with a72% isolated yield under optimized reaction conditions (80 degrees C, 2 h). After that, CMF was transformed into various novel esters ofHMF in excellent isolated yields (>85%) by reacting with a slight excess amount of the triethylammonium salt of various alkyl/arylcarboxylic acids under solvent-free conditions
Keywords: catalysis; cellulose; furanics; HMF-esters; renewable synthesis